REGULATION OF LAND OWNERSHIP FOR FOREIGN CITIZENS IN INDONESIA FROM AGRARIAN LAW PERSPECTIVE - Yanto, Nur Hairul Hari; Nasarudin, Muhammad (Progressive Law Review, 2021)
In the agrarian system, Article 21 paragraph 1 of the Basic Agrarian Law states that only Indonesian citizens have property rights. One of the examples of ownership rights is the right to land ownership or those that may have a relationship with the earth and space without differentiating between men and women as well as fellow Indonesian citizens, both native and descendants.